0D/1D/2D architectural Co@C/MXene composite for boosting microwave attenuation performance in 2–18 GHz. (30th June 2022) - Zou, Zhe; Ning, Mingqiang; Lei, Zhenkuang; Zhuang, Xueheng; Tan, Guoguo; Hou, Jianhua; Xu, Hui; Man, Qikui; Li, Jingbo; Li, Run-Wei
Abstract: Ti3 C2 Tx is considered a candidate for high-efficiency microwave absorption materials due to its adjustable electrical conductivity, low density and high specific surface area in recent years. However, the single absorption mechanism could not meet the practical requirements as the functional microwave absorbers. Herein, 0D/1D/2D architectures of Co@C/MXene with 0D Co nanoparticles, 1D carbon nanotubes (CNTs) and 2D Ti3 C2 Tx MXene nanosheets were rationally fabricated to enhance the microwave attenuation performance, in which Co@CNTs were in situ grown on Ti3 C2 Tx MXene nanosheets. By changing the amount of Ti3 C2 Tx MXene to optimize the impedance matching properties, the Co@C/M − 10 absorber exhibits excellent microwave attenuation performance with a minimum reflection loss of −50.5 dB at 5.9 GHz under a thickness of 4.0 mm. Meanwhile, the maximum effective absorption bandwidth (<−10 dB) of Co@C/M − 10 absorber can reach 5.8 GHz under 2.0 mm. The remarkable absorption performance can be ascribed to the synergistic effects of interface polarizations and magnetic loss. Moreover, the radar cross section (RCS) simulation was also performed via CST. Under the incident angle of 0°, the RCS reduction value of Co@C/M − 10 can reach 33.5 dBm 2 . This work provides a strategy for synthesizing MXene-based composite materials with tunable electromagnetic attenuation and wide absorption bandwidth performance. Graphical abstract: The 0D/1D/2D heterostructure Co@C/MXene composite composed of 0D Co, 1D carbon nanotubes and 2D MXene was fabricated through electrostatic self-assembly and high temperature heat treatment process, which exhibits the effective absorption bandwidth (EAB, <―10 dB) of 5.8 GHz (11.3–17.1 GHz) under 2.0 mm. Furthermore, the electromagnetic wave attenuation performance of Co@C/MXene under the real far-field condition was estimated by CST simulation, demonstrating the potential of Co@C/MXene in practical applications. Image 1 Highlights: 0D/1D/2D architectural Co@C/MXene composite was rationally constructed. By adjusting the content of MXene, the tunable electromagnetic parameters and boosted EMW attenuation performance were achieved. Co@C/M − 10 absorber exhibits a RL min of −50.5 dB and the EAB (<―10 dB) of 5.8 GHz. CST was utilized to simulate the RCS values of Co@C/MXene under real far-field conditions.